Sex hormones, adiposity, and metabolic traits in men and women: a Mendelian randomisation study - Loh, NY; Humphreys, E; Karpe, F; Tomlinson, JW; Noordam, R; Christodoulides, C (BioScientifica, 2022)
Objective Epidemiological and clinical studies have highlighted important roles for sex hormones in the regulation of fat distribution and systemic metabolism. We investigated the bidirectional associations between bioavailable serum testosterone (BioT) in both sexes and oestradiol (E2) in men and adiposity and metabolic traits using Mendelian randomisation (MR).